Toleransi Beragama Dalam Persfektif Al-Qur'an - Mujetaba Mustafa (LPPM IAIN Sorong, 2015)
This article elaborates tolerance in the perspective of Al-Quran. Minimally, there are two groups of ayat in holy texts discribing that, Al-Quran Al-Kafirun 1-6 and QS Yunus 40-41. In hermeunetic of QS al-Kafurun 1-6 and QS Yunus 40-41 we shoud undertand the spirit of Islam religion. The tolerance is built of quranic Text from the firs time in the world. So, the spirit of tolerance must be followed by Muslim community where ever and when ever. The basis of tolerance is act ofrespecting each other because Muhmmad saw was tolerant to people in community the religion in Madina the last time.